Lessons for Electric Utilities from COVID-19 Responses in Emerging Markets - Apfalter, Stefan (International Finance Corporation, Washington, DC, 2020)
The Coronavirus (COVID-19) pandemic and the resulting economic shutdown have severely depressed electricity demand across the globe, with acute consequences for the revenues and financial health of utilities, as well as smaller providers of utility services and off-grid companies. In many places, utility service providers also must manage the inability of consumers to pay for their services. Government support has been forthcoming, but utilities need to work closely with policymakers to ensure that programs are carefully designed in order to maintain ongoing system reforms, competitiveness, and affordability, and avoid long-lasting market disruptions. These support measures should avoid redundancy among sectors and ensure that resources are efficiently allocated and that welfare improvements are fairly distributed across the country in a sustainable manner. Investors must also understand changes to utilities’ finances and should work to support further reforms.